Novel synthetic route for (parent) phosphetanes, phospholanes, phosphinanes and phosphepanes. Issue 14 (20th March 2023) - Reichl, Stephan; Balázs, Gábor; Scheer, Manfred
Abstract : A novel synthetic route for (parent) phosphorus-containing cycloalkanes such as phosphetanes, phospholanes, 5 phosphinanes and phosphepanes and their organo-substituted derivatives is reported. For the first time the parent phospholane was synthesised. Abstract : A novel synthetic route for (parent) phosphorus-containing cycloalkanes such as phosphetanes, phospholanes, phosphinanes and phosphepanes is reported. By using [K(dme)2 ]2 [Cp*Fe(η 4 -P5 )] (I ) in combination with α, ω-dibromoalkanes C n H2 n Br2 [ n = 3–6], unique phosphetane, phospholane, phosphinane and phosphepane precursor complexes [Cp*Feη 4 -P5 (CH2 ) n ] [ n = 3–6] (2–5 ) are synthesised. They act as P-atom carriers and the corresponding phosphetane, phospholane, phosphinane and phosphepanes (6–9 ) can be released by nucleophiles i.e., potassium benzyl (KBn) or LiAlH4 . The latter enables the selective synthesis of parent cyclic secondary phosphines (10 ) in an easy and straightforward way, including the first parent phospholane (10b ).